Markov Modeling of Battery Cell Behavior Taking into Account Pulsed Discharge Recovery (European Journal of Pure and Applied Mathematics, 2021)
In this work, we modeled the behavior of a battery. After having formulated a Markovian model, we evaluated the delivered capacity as well as the gained capacity. We, likewise, evaluated the mean number of pulses and studied the asymptotic behavior and the variance of this mean number. As a last resort, we introduced an extension of the Markov model.